2023
DOI: 10.1111/ctr.14933
|View full text |Cite
|
Sign up to set email alerts
|

Short‐term clinical outcomes and predicted cost savings of dd‐cfDNA‐led surveillance after pediatric heart transplantation

Abstract: Background Endomyocardial biopsy (EMB)‐led surveillance is common after pediatric heart transplantation (HT), with some centers performing periodic surveillance EMBs indefinitely after HT. Donor derived cell‐free DNA (dd‐cfDNA)‐led surveillance offers an alternative, but knowledge about its clinical and economic outcomes, both key drivers of potential utilization, are lacking. Methods Using single‐center recipient and center‐level data, we describe clinical outcomes prior to and since transition from EMB‐led s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Several HT studies have demonstrated noninferiority of a ddcfDNA-based surveillance protocol compared with EMB due to its high negative predictive value (NPV) for clinically meaningful AR. [3][4][5][6] Additionally, the degree of ddcfDNA elevation correlates with severity and type of AR, and treatment of AR is followed by predictable decreases in ddcfDNA levels. 7,8 Data in adult HT recipients suggest that ddcfDNA may rise before histologic changes of AR, therefore capturing early rejection.…”
Section: Introductionmentioning
confidence: 99%
“…Several HT studies have demonstrated noninferiority of a ddcfDNA-based surveillance protocol compared with EMB due to its high negative predictive value (NPV) for clinically meaningful AR. [3][4][5][6] Additionally, the degree of ddcfDNA elevation correlates with severity and type of AR, and treatment of AR is followed by predictable decreases in ddcfDNA levels. 7,8 Data in adult HT recipients suggest that ddcfDNA may rise before histologic changes of AR, therefore capturing early rejection.…”
Section: Introductionmentioning
confidence: 99%